giúp với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(-1,6:\left(1+\dfrac{2}{3}\right)=-1,6:\dfrac{5}{3}=-\dfrac{8}{5}.\dfrac{3}{5}=\dfrac{-24}{25}\)
b)\(\left(\dfrac{-2}{3}\right)+\dfrac{3}{4}-\left(-\dfrac{1}{6}\right)+\left(\dfrac{-2}{5}\right)=-\dfrac{2}{3}+\dfrac{3}{4}+\dfrac{1}{6}-\dfrac{2}{5}=\dfrac{-40+45+10-24}{60}=\dfrac{-9}{60}=\dfrac{-3}{20}\)
c)\(\left(\dfrac{-3}{7}:\dfrac{2}{11}+\dfrac{-4}{7}:\dfrac{2}{11}\right).\dfrac{7}{33}=\left(\dfrac{-3}{7}.\dfrac{11}{2}+\dfrac{-4}{7}.\dfrac{11}{2}\right).\dfrac{7}{33}=\left[\dfrac{11}{2}\left(\dfrac{-3}{7}+\dfrac{-4}{7}\right)\right].\dfrac{7}{33}=\dfrac{-11}{2}.\dfrac{7}{33}=\dfrac{-7}{6}\)
d)\(\dfrac{-5}{8}+\dfrac{4}{9}:\left(\dfrac{-2}{3}\right)-\dfrac{7}{20}.\left(\dfrac{-5}{14}\right)=\dfrac{-5}{8}-\dfrac{4}{9}.\dfrac{3}{2}+\dfrac{1}{8}=\dfrac{-5}{8}+\dfrac{1}{8}-\dfrac{2}{3}=-\dfrac{7}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1 correct
2 success => only success
3 was released => released
4 correct
5 focused on => on
6 as a => a
7 correct
8 each others => others
9 satisfy with => satisfy
10 correct
11 correct
![](https://rs.olm.vn/images/avt/0.png?1311)
1 were - would you play
2 weren't studying - would have
3 had taken - wouldn't have got
4 would you go - could
5 will you give - is
6 recycle - won't be
7 had heard - wouldn't have gone
8 would you buy - had
9 don't hurry - will miss
10 had phoned - would have given
11 were - wouldn't eat
12 will go - rains
13 had known - would have sent
14 won't feel - swims
15 hadn't freezed - would have gone
![](https://rs.olm.vn/images/avt/0.png?1311)
e)
\(\left(x^2-1\right)\cdot\left(x^2+4x+3\right)=45\\ \Leftrightarrow x^4+4x^3+2x^2-4x-48=0\\ \Leftrightarrow\left(x^3+6x^2+14x+24\right)\cdot\left(x-2\right)=0\\ \Leftrightarrow\left(x^2+2x+6\right)\cdot\left(x+4\right)\cdot\left(x-2\right)=0\\ \Rightarrow\left[{}\begin{matrix}x+4=0\\x-2=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=-4\\x=2\end{matrix}\right.\)
d)
\(\left(x^2+3x+2\right)\cdot\left(x^2+5x+6\right)=72\\ \Leftrightarrow x^4+8x^3+23x^2+28x-60=0\\ \Leftrightarrow\left(x^3+9x^2+32x+60\right)\cdot\left(x-1\right)=0\\ \Leftrightarrow\left(x^2+4x+12\right)\cdot\left(x+5\right)\cdot\left(x-1\right)=0\\ \Rightarrow\left[{}\begin{matrix}x+5=0\\x-1=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=-5\\x=1\end{matrix}\right.\)